Popular Perceptions and Political Economy in the Contrived World of Harry Potter - Avichai Snir; Daniel Levy (Bar-Ilan University, Department of Economics, 2005)
Economic organization of the imaginary worlds depicted in popular literary works may be viewed as a mirror to public opinion on the economic organization of life. If a book becomes a best-seller, it is because the book conveys messages, feelings, and events the readers can relate to. In other words, the book's readers identify with the set of norms and rules that govern the development of the plot and the actions of its heroes. Therefore, a best seller, as a book that successfully relates to readers of its time, can teach us about the norms and beliefs of its audience. Following this line of thought, we use the method of deconstruction to analyze the highly successful J.K. Rowlings' Harry Potter series. Studying the books within their social context allows us to learn about people's norms and attitudes, and their perceptions of issues such as the role of government, the structure of financial markets, poverty and inequality, etc. Thus, by looking at the Potterian economy through magnifying glasses, we obtain a perspective on what people might view as a normal or perhaps as an ideal economic structure. In other words, we argue, that the economic and organizational structure of the imaginary Potterian economy can be viewed as an economic model. By studying the social and the economic structure of the Potterian model and its assumptions, we hope to obtain some insights on people's attitudes towards various social and economic issues. The Potterian economic model, we conclude, is not a coherent model that fits neatly one of the standard economic models. Instead, it appears to combine ingredients from various economic models.
Keywords: A13; A14; D73; P16; P48; Z11; Z13; 330; Political Economy; Social Attitude; Social Norm; Social Organization of Economic Activity; Perception; Harry Potter; Literature